PENGARUH PEMOTONGAN DENGAN DAN TANPA CAIRAN PENDINGIN TERHADAP DAYA POTONG PADA PROSES TURNING - Alfred Hara; I Nyoman Gede; Rudy Poeng (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2016)
In this study whether the effect of cuts without using coolant differ significantly by cutting use liquid cooling to the power cut. To get the effect these cuts do testing on a lathe with a cutting speed varied. The results of this study, based on cutting anlisis detected by the fifth variation of the cutting speed will affect the power cut. With the greater the cutting speed will increase cutting power, good for lathing process with and without coolant. The process of turning the cooling liquid tends to be greater influence on cutting power compared to the lathing process without coolant. Based anlisis regression and correlation with level of 5% error hypothesis test two directions is known that in the process of turning cutting speed without coolant does not affect the power cut amounted to 73.48%. While in the process of turning to liquid cooling effect on the cut of 97.56%. Keywords: Cut Speed, Coolant, turning, Power Cut